Gastrointestinal parasitism in Guinea Pigs (Cavia porcellus) from three Communities of Huancavelica, Perú - Carhuapoma-Delacruz, Víctor; Valencia–Mamani, Nicasio; Lizana–Hilario, Epifanio; Huaman-Jurado, Rodrigo; Zárate-Rendón, Daniel Alexis; Esparza, Mario (Revista Científica de la Facultad de Ciencias Veterinarias, 2022)
The parasites produced by protozoa and helminths constitute health problems in the productive raising of Guinea Pigs (GP), however, knowledge related to their etiology, dynamics of infection and epidemiology was limited. This makes it difficult to design optimal and cost-effective control programs. The presence of gastrointestinal parasites was identified in GP from the Communities of Huando, Mariscal Cáceres and Yauli, Huancavelica-Peru, determining the fauna, frequency, parasite load, degree of infection and its relationship with origins and sex. One hundred six GP of both sexes were sampled, 20 grames (g) of feces per animal were collected and analyzed by flotation-sedimentation coprological techniques, Modified Ziehl-Neelsen and Modified McMaster. The prevalence of endoparasites was 82.5 %: protozoa being more frequent with 82.7 % than Nematodes, with 38.5 %. Eimeria caviae had frequencies of 85.7; 80.0 and 83.3 % in the Community of Huando, Mariscal Cáceres and Yauli, respectively. Strongyloides spp., and Trichuris spp. presented frequencies of 35.7 and 28.6 % for Huando. E. caviae (12-30 %) and Cryptosporidium spp. (5-12 %) in GP from Huando and Mariscal Cáceres. The parasite load averages, expressed in oocysts per g for E. caviae were 1,029.17 in Huando, for Mariscal Cáceres 571.43 and in Yauli 1,126.67 the rest of the parasites presented load of eggs of minimum values with a low degree of infection (≤ 200 eggs per g). E. caviae, Cryptosporidium spp., and Strongyloides spp. were the most frequent with high parasitic loads and degree of infection in producing GP.